قراءة سيميائية في غلاف المجموعة القصصية (المكحلة ) أحمد يوسف عقيلة - إلطيف, تهاني عبد السلام محمد; قزيمة, فاطمة الطيب (Al-Qurtas, 2025)
قراءة سيميائية في غلاف المجموعة القصصية (المكحلة ) أحمد يوسف عقيلة